2018
DOI: 10.1016/j.cmi.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

ESCMID Study Group for Infections in Compromised Hosts (ESGICH) Consensus Document on the safety of targeted and biological therapies: an infectious diseases perspective (Soluble immune effector molecules [I]: anti-tumor necrosis factor-α agents)

Abstract: Prevention measures should be implemented to reduce the risk of latent tuberculosis or HBV reactivation among individuals receiving anti-TNF-α therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 137 publications
(97 reference statements)
0
108
1
5
Order By: Relevance
“…38 In particular, there are increased chances of severe infections in the skin, soft tissues, and joints, alongside increased risk of non-melanoma skin cancers. [39][40][41] Treatment with anti-TNF is also a risk factor contributing to latent tuberculosis (TB) reactivation. 42 In a recent review of 40 randomized controlled trials (RCTs), involving a total of 14,683 patients, TB reactivation occurred in 0.26% of the anti-TNF group compared with 0.00% in the control group.…”
Section: Limitations Of Parenteral Administration Of Anti-tnf Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 In particular, there are increased chances of severe infections in the skin, soft tissues, and joints, alongside increased risk of non-melanoma skin cancers. [39][40][41] Treatment with anti-TNF is also a risk factor contributing to latent tuberculosis (TB) reactivation. 42 In a recent review of 40 randomized controlled trials (RCTs), involving a total of 14,683 patients, TB reactivation occurred in 0.26% of the anti-TNF group compared with 0.00% in the control group.…”
Section: Limitations Of Parenteral Administration Of Anti-tnf Agentsmentioning
confidence: 99%
“…Anti‐TNF also associates with higher infection risks in patients with UC . In particular, there are increased chances of severe infections in the skin, soft tissues, and joints, alongside increased risk of non‐melanoma skin cancers . Treatment with anti‐TNF is also a risk factor contributing to latent tuberculosis (TB) reactivation .…”
Section: Introductionmentioning
confidence: 99%
“…This study reviewed and summarized prevention strategies, including screening, monitoring, immunization, prophylaxis, and management of infections associated with about 70 biologic and targeted therapies based on relevant guidelines, especially ESCMID Study Group for Infections in Compromised Hosts (ESGICH) Consensus document series published in 2018. [8][9][10][11][12][13] in preventing HBV reactivation in patients on anti-CD20 monoclonal antibodies. 32,33 Therefore, ESCMID recommends either tenofovir or entecavir-based regimens for antiviral therapy in both active and occult hepatitis B patients who are candidates for anti-CD20 targeted agents.…”
Section: Discussionmentioning
confidence: 99%
“…The European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Study Group for Infections in Compromised Hosts Consensus have reviewed articles and made recommendations to instruct clinicians on the strategies to prevent and manage infections associated with biologic and targeted immunomodulators. [8][9][10][11][12][13] In this review, we aim to focus on evidence-based strategies according to the latest guidelines to provide practitioners guidance regarding screening, chemoprophylaxis, vaccination, and management of infections in patients on biologic and targeted immunomodulators.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the PMS studies revealed risk factors of developing tuberculosis; past history and/or family history of tuberculosis, old tuberculosis by imaging studies, and positive tuberculin skin test or interferon-gamma release assay [1][2][3][4][5] . Analyses of data from clinical trials, national registries, and PMS studies demonstrated significantly higher risk of tuberculosis associated with infliximab and adalimumab compared to etanercept and rituximab 6,7) . Three-year follow-up Japanese PMS study of tocilizumab reported an incidence rate of 0.04/100 patient-years for tuberculosis 8) .…”
Section: B Haraouimentioning
confidence: 99%